Assessing genetic variability in Cycas dolichophylla (Cycadaceae) - Tâm, Nguyễn Minh; Trang, Nguyễn Thị Phương; Hiệp, Nguyễn Tiến; Lý, Trần Đình; Triest, Ludwig (Vietnam Journal of Biotechnology, 2008)
Journal of Biotechnology 3(1): 79-88, 2005